Long non-coding RNAs in female infertility: Advancing from molecular insights to clinical relevance - Tayyebeh Zamani-Badi; Azadeh Sadat Azadbakhsh; Saeedeh Ghazaey Zidanloo; Elaheh Seyed Hosseini; Mohammad Karimian; Hossein Nikzad (Clinical and Experimental Reproductive Medicine, 2026)
A broad range of genetic and epigenetic factors contributes to female infertility, a substantial proportion of which is related to ovulatory disorders. Any factor that disrupts the normal function of key ovarian components, including the follicle, the enclosed oocyte, and surrounding somatic cells, may contribute to female infertility. Investigating the molecular factors involved in folliculogenesis and reproductive pathways may substantially improve the treatment of diseases affecting the female reproductive system. Long non-coding RNAs (lncRNAs), as key regulators of molecular and biological processes, play important roles in ovarian function and female fertility. These effects are mediated through interactions with DNA, RNA, and proteins, and lncRNAs are involved in processes such as granulosa cell differentiation, follicular growth, and ovarian hormonal regulation. Altered lncRNA expression may contribute to reproductive disorders such as polycystic ovary syndrome, endometriosis, and primary ovarian insufficiency. In addition, several lncRNAs have been proposed as potential biomarkers for the diagnosis of female reproductive disorders and as novel therapeutic targets. However, many functional mechanisms of these molecules remain unclear. This review summarizes recent scientific findings on the role of lncRNAs in the pathophysiology of female infertility and evaluates their potential for the development of novel diagnostic and therapeutic approaches. A better understanding of these molecular pathways may support more effective strategies for managing and treating female infertility.